Alih Kode dan Campur Kode Pada Podcast “Rumah Pocong Ningrum” Channel Youtube Lentera Malam - Rositasari, Alivia; Muliyono, Nurwakhid; Susilawati, Lis (Jurnal Kiprah Pendidikan, 2025)
Code switching and code mixing in the the horror podcast “Rumah Pocong Ningrum” on the Lentera Malam YouTube channel is the purpose of this study.  This research applies descriptive qualitative methodology, with note taking technique as data collection tool. The findings of the analysis show the occurrence of internal code switching, or code switching between dialects of the same language.  This research also reveals the phenomenon of code-mixing, which includes the addition of additional language components in the form of bases, words, phrases, and clauses. The form determines the resulting code mix, which consists of inward code mix (local language inserted into Indonesian), outward code mix (foreign language inserted into Indonesian), and mixed code mix (when both are combined). This research investigates the causal factors of code-switching as well as the causal factors of code-mixing. This research adds to the repertoire of linguistics, especially sociolinguistics, by giving attention to the problem of code-switching and code-mixing in digital media, such as YouTube podcasts.